2015
DOI: 10.1245/s10434-015-4721-y
|View full text |Cite
|
Sign up to set email alerts
|

Single Institution Experience with Lymphatic Microsurgical Preventive Healing Approach (LYMPHA) for the Primary Prevention of Lymphedema

Abstract: Our transient lymphedema rate in this high-risk cohort of patients was 12.5%. Early data show that LYMPHA is feasible, safe, and effective for the primary prevention of breast cancer-related lymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 30 publications
1
93
0
Order By: Relevance
“…Bioimpedance spectroscopy (BIS) is one of the few techniques of body composition analysis which differentiates the extracellular fluid compartment from the total limb volume [27]. The use of BIS for clinical monitoring of the risk of lymphedema and of lymphedema progression is under increasingly wide application and has been validated in numerous prospective clinical studies [28, 29]. Multi-frequency BI analysis is based on the fact that the resistance to the flow of electric current through the body is inversely proportional to the volume of fluid in the tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Bioimpedance spectroscopy (BIS) is one of the few techniques of body composition analysis which differentiates the extracellular fluid compartment from the total limb volume [27]. The use of BIS for clinical monitoring of the risk of lymphedema and of lymphedema progression is under increasingly wide application and has been validated in numerous prospective clinical studies [28, 29]. Multi-frequency BI analysis is based on the fact that the resistance to the flow of electric current through the body is inversely proportional to the volume of fluid in the tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Conversion from a single site deep upper brachial injection to a subdermal injection of several aliquots of dye circumferentially in the medial upper arm resulted in superior visualization and preservation of uninvolved lymphatics. This represents an improvement over the report by Feldman et al where 5/35 patients were unable to undergo LVB because of the inability to identify suitable lymphatics. Our results are consistent with, and reveal a slight improvement over the lymphatic identification rate of 96% (75/78 patients) reported by Boccardo et al in their 4‐year follow‐up report.…”
Section: Discussionmentioning
confidence: 60%
“…Although it is inevitable that some lymphatics will be divided for oncologic control, ARM allows for differentiation of UE and breast drainage pathways. Prior studies evaluating reverse mapping have demonstrated success rates in identifying UE lymphatic channels from 61%‐71% . In patients undergoing ALND, ARM has facilitated lymphatic sparing in up to 67.3% of patients …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…procedure in the prevention of secondary arm lymphedema and LY.M.P.H.A. technique was included among the surgical procedures to prevent breast cancer related lymphedema [19][20][21][22] .…”
Section: Figure 4 -Lympha Technique At the Groin A -Tributary Omentioning
confidence: 99%